Clinical use of convalescent plasma in the COVID-19 pandemic: a transfusion-focussed gap analysis with recommendations for future research priorities - Al-Riyami, AZ; Schäfer, R; van den Berg, K; Bloch, EM; Estcourt, LJ; Goel, R; Hindawi, S; Josephson, CD; Land, K; McQuilten, ZK; Spitalnik, SL; Wood, EM; et al. (Wiley, 2020)
Background and objectives Use of convalescent plasma for coronavirus disease 2019 (COVID-19) treatment has gained interest worldwide. However, there is lack of evidence on its dosing, safety and effectiveness. Until data from clinical studies are available to provide solid evidence for worldwide applicable guidelines, there is a need to provide guidance to the transfusion community and researchers on this emergent therapeutic option. This paper aims to identify existing key gaps in current knowledge in the clinical application of COVID-19 convalescent plasma (CCP). Materials and methods The International Society of Blood Transfusion (ISBT) initiated a multidisciplinary working group with worldwide representation from all six continents with the aim of reviewing existing practices on CCP use from donor, product and patient perspectives. A subgroup of clinical transfusion professionals was formed to draft a document for CCP clinical application to identify the gaps in knowledge in existing literature. Results Gaps in knowledge were identified in the following main domains: study design, patient eligibility, CCP dose, frequency and timing of CCP administration, parameters to assess response to CCP treatment and long-term outcome, adverse events and CCP application in less-resourced countries as well as in paediatrics and neonates. Conclusion This paper outlines a framework of gaps in the knowledge of clinical deployment of CPP that were identified as being most relevant. Studies to address the identified gaps are required to provide better evidence on the effectiveness and safety of CCP use.